1988
DOI: 10.3109/08977198809000242
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cells Synthesize Basic Fibroblast Growth Factor and Transforming Growth Factor Beta

Abstract: Endothelial cells, including human umbilical vein endothelial cells (HUVEC), bovine aortic endothelial cells (BAEC), and bovine capillary endothelial cells (BCEC) in culture synthesize basic fibroblast growth factor (bFGF) and transforming growth factor type beta (TGF-beta). Basic FGF was cell-associated and synthesis was demonstrated by (i) the presence of bFGF mRNA species, (ii) binding to heparin-Sepharose and elution at 1.5 M NaCl, (iii) cross-reactivity with anti-bFGF antibodies when analyzed by electroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
1

Year Published

1990
1990
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(45 citation statements)
references
References 48 publications
2
42
0
1
Order By: Relevance
“…The mechanisms that regulate SMC modulation to the synthetic and proliferative state has been the focus of several laboratories. Research in this area revealed that a number of cytokines are involved in this transition, including PDGF and TGF-b (Collins et al, 1987;Hannan et al, 1988;Sato et al, 1990;Ross et al, 1993). Nevertheless, it appears certain that multiplicity of molecular pathways are involved in pathological SMC replication associated with arterial lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms that regulate SMC modulation to the synthetic and proliferative state has been the focus of several laboratories. Research in this area revealed that a number of cytokines are involved in this transition, including PDGF and TGF-b (Collins et al, 1987;Hannan et al, 1988;Sato et al, 1990;Ross et al, 1993). Nevertheless, it appears certain that multiplicity of molecular pathways are involved in pathological SMC replication associated with arterial lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is reasonable to suggest that the endothelium might be used as a template for recruitment and migration of presumptive SMCs and perhaps might regulate this process. Heparin-like molecules Fritze et al, 1985;Castellot et al, 1982) and several growth factors such as PDGF, bFGF, and TGFb are secreted by the endothelium (Collins et al, 1987;Hannan et al, 1988;Sato et al, 1990). These and other factors may play a role in recruitment and migration of undifferentiated SMC precursors in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…While it is possible that the airway cells contribute to the level of TGF-# in lung lymph, the level is tenfold greater than that found in epithelial lining fluid, suggesting that TGF-# is also produced by other cells in the interstitium and/or vascular wall. Endothelial cells (30) and lymphocytes (31,32) have been reported to produce TGF-# in vitro and may also contribute to the TGF-4 in lung lymph.…”
Section: Discussionmentioning
confidence: 99%
“…51 Important growth inhibitors produced by the endothelium are heparin, heparin sulfates, transforming growth factor-β, and most likely nitric oxide. 52,53 On the other hand, endo thelial cells can also produce growth factors such as basic fibroblast growth factor, platelet-derived growth factor (PDGF), and possibly also endothelin ( Figure 6). 54,55 These factors contribute to proliferative re sponses, at least under certain conditions, whereas it has to be assumed that under normal conditions inhib itory stimuli prevail.…”
Section: Endothelial Regulation Of Vascular Growthmentioning
confidence: 99%